Św. Ambroży Autpert, Książeczka o konflikcie wad i cnót - Barczak, Michał (Vox Patrum, 2025)
The first translation into Polish of the work of Ambrose Autpert, Libellus de conflictu vitiorum atque virtutum missus ad Lantfredum presbyterum et abbatem in Baioaria constitutum with commentary.